Influence of couple stress and magnetic fluid on the performance of step slider bearing - Chauhan, Dipali K.; Patel, Jimit R.; Deheri, G.M. (Zielona Góra: Uniwersytet Zielonogórski)
This theoretical investigation delves into the performance of step slider bearings, considering the influence of couple stress and magnetic fluid as the lubricating medium. Employing a non-linear model for magnetic field intensity aims to optimize bearing performance. Modifying the Reynolds equation for step slider bearings incorporates theories from Neuringer and Rosensweig for magnetic fluid flow dynamics and the Stokes micro-continuum model to account for couple stress effects.
Keywords: step slider bearing; load capacity; magnetic fluid; couple stress; magnitude of magnetic field